Self Care Management Pasien Hemodialisa Ditinjau Dari Dukungan Keluarga Di Rsud Dr.Soetomo Surabaya - DYAH WIJAYANTI; Dinarwiyata Dinarwiyata; Tumini Tumini (coba, 2018)
Self care management in patients with chronic renal failure who undergoing hemodialysis is a positive effort of patients to find and participate in their health services to optimize health, prevent complications, control symptoms, develop medical resources, minimize disturbance in diseases that can interfere with life. Family support is very important in the care of hemodialysis patients. The purpose of this study is to analyze the relationship of family support with self-care management of hemodialysis patients. The research method used analytic description with cross sectional approach. The population involved in this study were patients in the hemodialysis room of RSUD Dr.Soetomo Surabaya, with a sample size of 52 respondents, using consecutive sampling. Independent variable in this research is family support and dependent variable is self care management. Data collection using a family support questionnaire and modified hemodialysis patient self care measurement scale. Data were analyzed using spearman rho, with significant level p less than 0,05. The results showed that family support affects the self-care management of hemodialysis patients (p = 0.01). Family support affects the self-care management of hemodialysis patients in the hemodialysis chamber of Dr.Soetomo Hospital Surabaya. The importance of family support is necessary in treating hemodialysis patients for self-care management including monitoring of diet, stress management, safe diet, exercise, good habits, shunt care, diet therapy and observation of care instructions.